EFL PRE-SERVICE TEACHERS’ ANXIETY DURING TEACHING PRACTICE - Zaki, Leil Badrah; Salsabila, Annisa (Universitas Muhammadiyah Metro, 2024)
The struggles that currently being the research interest in education is Pre-Service Teacher Anxiety. The anxiety can be seen not only “before” and “after”, but also